Contamination by neonicotinoid insecticides in barn owls (Tyto alba) and Alpine swifts (Tachymarptis melba) - Humann-Guilleminot, Ségolène; Laurent, Shirley; Bize, Pierre; Roulin, Alexandre; Glauser, Gaétan; Helfenstein, Fabrice (The Science of the total environment, 2021)
Monitoring the extent to which wildlife is exposed to the broadly used neonicotinoid insecticides (NNIs) is essential to assess their potential negative effects on biodiversity. Birds are good subjects to assess such exposure, because they inhabit various habitats and they feed at different trophic levels. However, so far, most studies have focused on the contamination of granivorous species. In this study, we assess the concentrations of five NNIs (acetamiprid, clothianidin, imidacloprid, thiacloprid, thiamethoxam) in the carnivorous Barn owl (Tyto alba), and the insectivorous Alpine swift (Tachymarptis melba). NNIs were measured in the Barn owl in feathers collected from nestlings in 2012 (n = 49 broods) and adults in 2016 (n = 58 individuals), and in the Alpine swift from feathers collected from 50 pooled nestling samples from 50 nests between 2004 and 2017 (nestlings raised in five different nests over ten years; n = 50 broods), plasma samples from adults in 2018 (n = 15), and food boluses collected from nestling provisioning adults in 2018 (n = 12). We found that 69% and 56.9% of Barn owl feathers from nestlings and adults respectively contained at least one NNI at measurable concentration. Mean ± SE and median concentrations (in ppb) of total NNIs were 0.66 ± 1.13 and 0.42 for nestlings, and 0.17 ± 0.57 and 0.04 for adults. In the Alpine swift, although we detected no NNI in nestling feathers, we found that 75% of food boluses and 20% adult plasma samples contained at least one NNI at measurable concentration. Mean ± SE and median concentrations (in ppb) of total NNIs were 0.24 ± 0.20 and 0.24 in food boluses, and 0.06 ± 0.13 and 0 in plasma. In view of these results, further research is warranted to determine the extent of contamination in non-granivorous birds and their potential effects. [Display omitted] •Exposure to neonicotinoid insecticides (NNIs) is poorly studied in non-granivorous birds.•NNIs quantified from feathers of nestlings and adult’s Barn owls.•NNIs quantified from nestlings’ feathers, food boluses and plasma of adults’ Alpine swifts.•In Barn owls, quantifiable concentrations in 69% of nestling feathers and 57% of adult feathers.•No NNIs in Alpine swift nestling feathers, but in 75% of food boluses and 20% of plasma.